Effect of Transport Density on Greater Amberjack (Seriola dumerili) Stress, Metabolism, Antioxidant Capacity and Immunity - Liu, Hongyan; Fu, Zhengyi; Yu, Gang; Ma, Zhenhua; Fu, Zhilu (Frontiers in Marine Science, 2022)
This study sought to characterize the effect of density stress on greater amberjack (Seriola dumerili) survival to determine an optimal transport density. To achieve this, this experiment simulated the transport conditions of fish (body length: 4.09 ± 1.00 cm; weight: 0.9 ± 0.05 g) using closed oxygen transport at 5 different densities (D1 = 1.125 kg/m3, D2 = 2.25 kg/m3, D3 = 3.375 kg/m3, D4 = 4.5 kg/m3, and D5 = 6.75 kg/m3) for 8 hours, after which biochemical indicators, stress, metabolism, and antioxidant capacity were evaluated. After 8h, only the D1 and D3 groups exhibited survival rates above 90%. The pH of the water decreased with density, whereas the ammonia nitrogen and nitrite increased with density. Cortisol (COR) levels were not significantly different among all the groups, but tended to increase with increasing density. In this study, COR is a relatively stable index with the increase in density, but in D3 group, the change of COR will not cause the change of immune-related genes, so COR can inhibit the expression of immune genes within a certain density. The D3 density group exhibited the highest catalase (CAT) and glutathione peroxidase glutathione peroxidase (GSH‐PX) levels. In addition, the expression levels of immune related factor interleukin-1β (IL-1β), tumor necrosis factor (TNF-α), major histocompatibility complex (MHC-1) and nuclear factor kappa-B (NF-KB1) were the lowest in D3 density group. The density of fish during transportation significantly affects water quality, metabolism, and immunity. During transportation, assuming that the plastic bags are airtight to ensure aerobic conditions and that the transportation time is within 8 h, transport density should be maintained at approximately 3.375 kg/m3.